Effect of processing temperature on electrophoretic deposition (EPD)-derived bioactive composite coatings for metallic bone implants - Azari, Rezvan; Boccaccini, Aldo R. (Surfaces and Interfaces, 2025)
Electrophoretic deposition (EPD) is an advanced shaping technique used for obtaining biomedical coatings at room temperature. This research is intended, for the first time, to investigate the effect of the working temperature on the suspension behavior and quality of bioactive glass-chitosan (BGCS) composite coatings obtained by EPD on metallic substrates. To accomplish this, BGCS coatings were electrophoretically deposited on stainless steel planar foils at five working temperatures; from ambient temperature to below the vaporization point of the solution (∼ 83.1 °C). The successful incorporation of BG particles (∼4 µm) and CS in all coatings was confirmed by FTIR and EDS analyses. A comprehensive study of electrical-physical properties of BGCS suspensions at different temperatures revealed an increasing trend in electrophoretic mobility (µ), suspension conductivity (σ), and current density (J) with temperature rise. However, the zeta potential (ζ), which is a measure of suspension stability, recorded its highest level (43.53 ± 1.48 mV) at 35 °C. Furthermore, at 35 °C, the deposition weight verified the highest deposition yield with the lowest standard deviation (1.29 ± 0.07 mg.cm-2). SEM micrographs showed that BG particles were homogenously distributed in the CS matrix at room temperature. By increasing the temperature to 35 °C the proportion of bioactive particles in the coating grew tremendously, however at temperatures higher than 45 °C the quality of deposited BGCS coatings started to decrease. The BGCS-35 and BGCS-45 coatings exhibited the highest adhesion strength (classes 2 and 3) among other coatings, possibly due to the incorporation of more BG particles and thus a denser and stiffer microstructure. Correspondingly, a temperature of around 35 °C is considered the best working temperature for the deposition of advanced BGCS composite coatings for metallic implants.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Bioactive glass; Chitosan; Composite coating; Electrophoretic deposition; Metallic implants; Temperature

Enhancing the Antibacterial Properties of Chitosan Coatings: Ag@Chitosan and Chitosan from Insects - Marsico, Michela; Azari, Rezvan; Curcio, Mariangela; Teghil, Roberto; Triunfo, Micaela; Falabella, Patrizia; Boccaccini, Aldo R.; De Bonis, Angela (Coatings, 2024)
In this study, the electrophoretic deposition (EPD) technique was used to prepare chitosan-based coatings with enhanced antibacterial activity suitable for bone implant applications. We designed, prepared, and compared the physico-chemical and biological properties of coatings obtained with commercial chitosan, chitosan enriched with silver nanoparticles, and chitosan obtained from insects. With the aim to consider the issue of sustainability, silver nanoparticles were directly prepared in the chitosan solution by laser ablation via a liquid technique, avoiding the use of chemicals and limiting the production of wastes. Moreover, a sustainable source of chitosan, such as Hermetia Illucens exuviae, was considered. The EPD process was optimized by adjusting parameters like voltage and deposition time to achieve ideal coating thickness and adhesion. The prepared films were characterized by spectroscopic and microscopic techniques such as SEM, XRD, and FTIR. Antimicrobial tests against E. coli and S. aureus revealed that silver nanoparticles enhanced the antibacterial properties of the polymer, whereas the biological evaluation using the WST8 test on MG63 human osteoblast-like cells showed that all coatings were non-toxic. Finally, chitosan obtained from insect showed comparable properties with respect to the commercial polymer, suggesting it could replace seafood-derived chitosan in biomedical applications, whereas the Ag@chitosan composite demonstrated superior antibacterial activity without compromising its biocompatibility.
CRIS-Team Scopus Importer:2024-09-06
Keywords: Ag NPs; antibacterial activity; chitosan; coating; electrophoretic deposition